(untitled) (Historia, 2021)
To most South African readers a book about English daily life in the Middle Ages must epitomise almost everything they dislike most about history. On the other hand, a book that makes a teenage boy who lives to play rugby turn off the TV must have something going for it! The book in question is Lacey and Danziger’The year 1000, and its immense readability teaches a lesson most South African historian urgently need to learn.